Exosomal miRNAs as Potential Biomarkers for Preeclampsia: miR-1283 Has the Highest Expression, while miR-152-3p Has the Lowest Expression - Sumawan, Herman; Giantari, Ifrinda; Mubarika, Sofia; Hadiati, Diah Rumekti; Pradjatmo, Heru (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Preeclampsia management is necessary, as it is one of the leading causes of death during pregnancy. Exosomal microRNAs (miRNAs) can serve as biomarkers for early detection, diagnosis, and prognosis of preeclampsia. NanoStrings is an effective method for identifying exosomal miRNA due to their high sensitivity and ability to work with small amounts of miRNA; however, the analysis using this method for determining preeclampsia biomarker is still limited. Therefore, this study was conducted to utilize the NanoStrings method in identifying preeclampsia biomarkers related to its underlying pathophysiology.METHODS: This study involved 12 pregnant women at 20–40 weeks of gestation, including 6 preeclampsia women and 6 normotension women. The miRNAs from plasma exosomes were processed using NanoStrings method with NanoString nCounter SPRINT Profiler. Enrichment analysis of The Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathways were performed to examine the pathophysiological pathways of preeclampsia, using the DIANA–miRPath v3.0.RESULTS: Forty-eight miRNAs were downregulated and 7 were upregulated (miR-1283, miR-613, miR-520a-3p, miR-3185, miR-556-3p, miR-1973, and miR-598-3p) in women with preeclampsia. The highest expression was observed in miR-1283 (log fold-change: 3.69) and the most lowest expression was in miR-152-3p (log fold-change: 1.41). Enrichment analysis showed that the most upregulated miRNAs pathways was estrogen signaling pathway, and the most downregulated was Hippo signaling pathways.CONCLUSION: miR-1283 has the highest expression, while and miR-152-3p has the lowest expression in preeclampsia women. These miRNAs are shown to be linked to specific pathways, shedding light on the pathophysiology of preeclampsia, and may serve as promising biomarkers.KEYWORDS: exosomes, biomarker, miRNAs, pathophysiology, preeclampsia, pregnancy